2015
DOI: 10.1038/ncomms9950
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition of olfactory bulb granule cells accelerates odour discrimination in mice

Abstract: Granule cells are the dominant cell type of the olfactory bulb inhibiting mitral and tufted cells via dendrodendritic synapses; yet the factors regulating the strength of their inhibitory output, and, therefore, their impact on odour discrimination, remain unknown. Here we show that GABAAR β3-subunits are distributed in a somatodendritic pattern, mostly sparing the large granule cell spines also known as gemmules. Granule cell-selective deletion of β3-subunits nearly abolishes spontaneous and muscimol-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 49 publications
4
64
0
Order By: Relevance
“…Second, many studies investigated the role of adult SVZ neurogenesis by depleting NSC and/or altering the properties of the neurons themselves at the level of their migration, survival, integration, and/or electrophysiological activity (Mouret et al, 2009;Abraham et al, 2010;Alonso et al, 2012;Gschwend et al, 2015;Nunes & Kuner, 2015;Wang et al, 2015). Second, many studies investigated the role of adult SVZ neurogenesis by depleting NSC and/or altering the properties of the neurons themselves at the level of their migration, survival, integration, and/or electrophysiological activity (Mouret et al, 2009;Abraham et al, 2010;Alonso et al, 2012;Gschwend et al, 2015;Nunes & Kuner, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, many studies investigated the role of adult SVZ neurogenesis by depleting NSC and/or altering the properties of the neurons themselves at the level of their migration, survival, integration, and/or electrophysiological activity (Mouret et al, 2009;Abraham et al, 2010;Alonso et al, 2012;Gschwend et al, 2015;Nunes & Kuner, 2015;Wang et al, 2015). Second, many studies investigated the role of adult SVZ neurogenesis by depleting NSC and/or altering the properties of the neurons themselves at the level of their migration, survival, integration, and/or electrophysiological activity (Mouret et al, 2009;Abraham et al, 2010;Alonso et al, 2012;Gschwend et al, 2015;Nunes & Kuner, 2015;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…To mark such age-matched cohort of newborn neurons in 4D À and 4D + mice, we then crossed the homozygous 4D À and 4D + lines with RCE GFP-flox+/+ mice (Miyoshi et al, 2010), thus, labeling nestin-CreERt2+ NSC upon Tam administration by GFP, irrespective from the presence or absence of RFP. 4D-derived granule neurons expressed the presynaptic vesicular GABA transporter VIAAT that colocalized with the post-synaptic marker gephyrin (Nunes & Kuner, 2015; Fig 3C). Morphometric and 3D-Sholl analyses revealed that spine density (0.36 AE 0.02 vs. 0.33 AE 0.03 spines/lm, 4D À and 4D + , respectively, P = 0.44), total dendritic length (0.78 AE 0.6 and 0.66 AE 0.8 mm, P = 0.26), and arborization (intersections as a function of distance from the soma F (1,28) = 0.61, P = 0.44) were comparable in granule cells derived from 4D À and 4D + NSC ( Fig 3B) and fitting well with previous reports (Abraham et al, 2010;Scotto-Lomassese et al, 2011;Breton-Provencher et al, 2016).…”
Section: Expands Nsc Without Inducing Their Depletion and Increasementioning
confidence: 93%
See 1 more Smart Citation
“…Despite the fact that GCs make up the largest neuronal population in the OB with neurochemically distinct subtypes, little is known about their functional heterogeneity. Studies aimed at addressing their roles in sensory information processing and odor behavior have usually considered them as a homogeneous population of interneurons [4,5,18]. Using in vivo two-photon imaging of GCaMP6s-infected GCs, we identified two types of GCs based on their level of spontaneous activity and their responses to odor stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…They establish reciprocal dendro-dendritic synapses with the lateral dendrites of principal neurons and play a major role in odor information processing by synchronizing principal cell activity via lateral and recurrent inhibitions [2,3]. The synchronization of principal neurons by GCs plays an important role in neuronal pattern separation by improving odor discrimination and disambiguating overlapping sensory maps evoked by similar odorants [4,5]. In vivo twophoton Ca 2+ imaging revealed, however, that odor responses by GCs are temporally and spatially heterogeneous [6].…”
Section: Introductionmentioning
confidence: 99%